What are effective interventions for chronic or recurrent yeast vaginitis?. Issue 6 (June 2017) - Kamara, Feremusu; Olotu, Olusesan; Otolorin, Abiodun; Rabilall, Ryan
Abstract : EVIDENCE‐BASED ANSWER : Induction of clinical remission with oral fluconazole followed by once‐weekly suppressive therapy for 6 months decreases recurrence of yeast vaginitis during suppression by 19% (number needed to treat [NNT]=6) compared with placebo (SOR: A, meta‐analysis of RCTs). Intravaginal nystatin for 14 days monthly for 6 months is as effective as once‐weekly oral fluconazole suppression, but is more effective in cases caused by Candida glabrata (SOR: B, single RCT). When measuring short‐term (1 month) outcomes in patients with recurrent disease, boric acid suppositories are more effective than nystatin, but similar to fluconazole. In the subset of cases caused by C glabrata, boric acid is more likely to be effective than fluconazole (SOR: B, systematic review not limited to RCTs).